MicroRNAs as novel targets and tools in cancer therapy - Abba, Mohammed L.; Patil, Nitin; Leupold, Jörg; Utikal, Jochen; Allgayer, Heike (Cancer letters, 2017)
MicroRNAs (miRNAs) are currently experiencing a renewed peak of attention not only as diagnostics but also especially as highly promising novel targets or tools for clinical therapy in several different malignant diseases. Moreover, the recent discovery of competing endogenous RNAs (ceRNAs) as novel miRNA-regulators has contributed exciting insights in this regard. Therefore, this review summarizes and discusses the latest findings on (1) how miRNAs have become therapeutic targets of diverse synthetic antagonists, (2) how novel endogenous regulators of miRNAs such as ceRNAs or pseudogenes could emerge as therapeutics scavenging oncogenic miRNAs and (3) how miRNAs themselves are already, and will increasingly be, used as therapeutics. Recent advances on the importance of miRNA-target affinity and the subcellular localization of miRNAs are also discussed. The potential of these developments in different tumor entities and particular hallmarks of cancer such as metastasis, disease progression, interactions with the tumor microenvironment, or cancer stem cells are equally highlighted.
Available online 1 April 2016
Gesehen am 20.09.2018